UNCOVERING AND HETEROGENEITY IN RISK PERCEPTIONS OF DRAGON FRUIT FARMERS’ IN BINH THUAN, VIETNAM - Nguyen Thi Thuy Dung; Truong Thi Thanh Phuong; Stijn Speelman (My University, 2025)
UNCOVERING AND HETEROGENEITY IN RISK PERCEPTIONS OF DRAGON FRUIT FARMERS’ IN BINH THUAN, VIETNAM
Keywords: Risk perceptions; Dragon fruit farmers; Binh Thuan